Validation of T-Track® CMV to assess the functionality of cytomegalovirus-reactive cell-mediated immunity in hemodialysis patients - Banas, Bernhard; Krüger, Bernd; Krämer, Bernhard (BMC immunology, 2017)
Uncontrolled cytomegalovirus (CMV) replication in immunocompromised solid-organ transplant recipients is a clinically relevant issue and an indication of impaired CMV-specific cell-mediated immunity (CMI). Primary aim of this study was to assess the suitability of the immune monitoring tool T-Track® CMV to determine CMV-reactive CMI in a cohort of hemodialysis patients representative of patients eligible for renal transplantation. Positive and negative agreement of T-Track® CMV with CMV serology was examined in 124 hemodialysis patients, of whom 67 (54%) revealed a positive CMV serostatus. Secondary aim of the study was to evaluate T-Track® CMV performance against two unrelated CMV-specific CMI monitoring assays, QuantiFERON®-CMV and a cocktail of six class I iTAg™ MHC Tetramers.
Published: 7 March 2017
Gesehen am 14.09.2018